Tailoring the Emission Behavior of WO3 Thin Films by Eu3+ Ions for Light-Emitting Applications - V Kavitha; V. Biju; K.G. Gopchandran; R. Praveena; C.K. Jayasankar; Wanichaya Mekprasart; Kanokthip Boonyarattanakalin; Wisanu Pecharapa; V.P. Mahadevan Pillai (Nanomaterials, 2022)
ion concentration.
Keywords: Transition Metal Oxide Nanomaterials; ZnO doping and properties; Gas Sensing Nanomaterials and Sensors